Essentials of early english : - Smith, Jeremy J. (Routledge, 2004)
Completely revised and updated, this new edition improves the highly successful Essentials of Early English that went before it. In Essentials of Early English Jeremy Smith presupposes almost no knowledge whatsoever and covers the vast subject in one neat volume.